2013
DOI: 10.1016/j.autneu.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in the hindbrain detect glucoprivation and regulate gastric motility

Abstract: Glucoprivation is a strong signal for the initiation of gastrointestinal contractions. While this relationship between utilizable nutrient levels and gastric motility has been recognized for more than 100 years, the explanation of this phenomenon has remained incomplete. Using widely differing approaches, recent work has suggested that the hindbrain is responsible for this chemoreflex effect. Surprisingly, astrocytes may be the main glucodetector elements under hypoglycemic conditions. Our own work using in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 72 publications
0
35
4
Order By: Relevance
“…NST astrocytes have been suspected of having a sensitivity to acute glucoprivation (78). This concept was supported by the work of Marty et al (45,46), as well as our own (47,49), showing that astrocytes may be essential to the detection and initiation of physiological reactions to rapid reductions in glucose availability to the brain. The anatomical relationships between the vascular supply, glial cells, and the neuropil certainly suggest that astrocytes occupy a "favored" (i.e., gateway) position from the perspective of monitoring material flux into the brain.…”
Section: Perspectives and Significancementioning
confidence: 72%
See 2 more Smart Citations
“…NST astrocytes have been suspected of having a sensitivity to acute glucoprivation (78). This concept was supported by the work of Marty et al (45,46), as well as our own (47,49), showing that astrocytes may be essential to the detection and initiation of physiological reactions to rapid reductions in glucose availability to the brain. The anatomical relationships between the vascular supply, glial cells, and the neuropil certainly suggest that astrocytes occupy a "favored" (i.e., gateway) position from the perspective of monitoring material flux into the brain.…”
Section: Perspectives and Significancementioning
confidence: 72%
“…The advantage of such a system in the management of a physiological emergency is that it retains its sensitivity to the defended parameter under practically all other physiological circumstances (20,51,61,74) This exclusivity of CRR circuitry can help identify CRR vs. non-CRR metabolic and feeding control elements. CRR circuit elements are probably not affected by, for example, leptin or ␣-melanocyte-stimulating hormone (␣-MSH) inputs, while non-CRR regulatory feeding and metabolic control elements are biased in their response to glucoprivic stimuli in the presence of signals corresponding to repletion state (20,51,61,74).Recent data from our laboratory as well as others (36,45,47,49) suggest that detection of a low-glucose state by brain stem astrocytes could be the trigger to the initiation of CRR. For example, transgenic mice in which GLUT2 transporter (a critical component of most glucodetection mechanisms) has been knocked out, do not increase glucagon secretion in response to hypoglycemia (i.e., one of the components of the CRR).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The strong excitatory input from the C1 cells to DMV neurons suggests that subsets of C1 cells produce GI stimulation (52). In theory, some of these C1 neurons could be hypoglycemia responsive since glucoprivation is a strong signal for the initiation of GI contractions (120). C1 cell lesions reduce the plasma epinephrine increase caused by administration of 2-deoxyglucose by ϳ75% (110).…”
Section: Contribution Of the C1 Neurons To Glucoprivic Responsesmentioning
confidence: 99%
“…Although the Marty et al (2005) report did not demonstrate that astrocytes were directly sensitive to or activated by low glucose, it implicated astrocytes in the central mechanism, which triggers glucagon release in response to hypoglycaemia. Recent studies also suggested that astrocytes located within the nucleus of the solitary tract, which is the key relay of the visceral primary afferents, are glucosensitive and potentially could contribute to the regulation of glucose levels in the body [35,36]. It has been further demonstrated [37] that the effect of glucoprivation (central administration of 2-deoxyglucose) on the activity of the neurones of the nucleus of the solitary tract and the dorsal motor nucleus of the vagus nerve can be blocked by fluorocitrate.…”
Section: Central Glucose Sensitivitymentioning
confidence: 99%